Career decision self-efficacy Item Bank: A Simulation study - Azpilicueta, Ana Estefanía (2022)
The transformation of the current world of work, determined by technological advances, affects and challenges the career decision-making process. To face these changes, the career self-management model, derived from social cognitive career theory, offers an optimal framework that allows studying the career adaptive behaviors that favor the preparation for career decision-making. In order to obtain a measure for the core construct, career decision-making self-efficacy, we elaborated an item bank from the selection of reagents from two scales widely used in the field for its estimation. Item analysis was performed from the item response theory. The results evidenced the unidimensionality of the item pool, with difficulty indexes and ability levels covering most of the measured continuum. As regard reliability indexes (persons and items), we observed that the allocation of persons and items might be reproduced in a predictable way. Global fit of items was suitable in most of them. We also performed two analyses of the evidence of the validity of the scores obtained through the Career Decision Making Self-Efficacy-Item Bank. We carried out a simulation study to determine the real level of ability of the subjects, providing information on the quality of the item bank developed to accurately assess career decision self-efficacy. Thus, we conducted a concurrent validity evidence study to establish test-criterion relationships between career decision self-efficacy and the more significant outcome variables of the career decision-making process: career decision, career indecision, and decisional anxiety. In summary, we developed, calibrated, and validated the first item bank to estimate the central construct of the career decision-making process, which is the first step to develop a Computerized Adaptive Test. Based on this technology, personalized evaluations of specific skills or traits such as career decision self-efficacy can be obtained and incorporated into computer-assisted career guidance systems.